Rancang Bangun Mesin Extruder Plastik - Nurzaman, Runo; Noubnome, viktor; Dirja, Iman (Universitas Muhammadiyah Metro, 2024)
This research explores the potential of a plastic extruder machine as a solution to address plastic waste by utilizing high temperatures to melt and form plastic blocks. The machine aims to determine the optimal temperature for the production of plastic pellets. Despite initially producing plastic liquid, the machine is expected to effectively reduce plastic waste. The machine specifications involve an electric motor, gearbox, melting furnace, intake, melting spiral, output, pulley, and V-belt. Analysis of electric motor planning determines the required power. Gearbox planning involves gearbox ratio and required torque. Planning for pulleys and V-belts is conducted to transmit power from the motor to the machine's drive system. Planning for shafts and bearings was also carried out. The plastic extruder machine holds promise as a significant solution for plastic waste recycling. The manufacturing cost of the machine is found to be Rp17,349,350 and can be further reduced with a more optimal design. Recommendations for future research include enhancing detailed analysis and utilizing a richer set of references.